Synthesis, crystal structure with free radical scavenging activity and theoretical studies of Schiff bases derived from 1-naphthylamine, 2,6-diisopropylaniline, and substituted benzaldehyde - Oladipo, Segun Daniel; Yusuf, Tunde Lewis; Zamisa, Sizwe Joshua; Tolufashe, Gideon Femi; Olofinsan, Kolawole Ayodapo; Tywabi-Ngeva, Zikhona; Mabuba, Nonhlangabezo (European Journal of Chemistry, 2021)
Three Schiff bases 1-(4-chlorophenyl)-N-(naphthalen-1-yl)methanimine (1), 1-(4-methoxy phenyl)-N-(naphthalen-1-yl)methanimine (2), and 1-(4-chlorophenyl)-N-(2,6-diisopropyl phenyl)methanimine (3) were synthesized and characterized by elemental analysis, 1H and 13C NMR, FT-IR and UV-Visible spectroscopic techniques. The crystal structure of compound 3 was obtained and it revealed that the compound crystallized in a monoclinic space group P21/n and there exists an intermolecular hydrogen bond in a phenyl-imine form with C-H⋯N. Crystal data for C19H22ClN: a = 7.28280(10) Å, b = 9.94270(10) Å, c = 24.0413(2) Å, β = 97.0120(10)°, V = 1727.83(3) Å3, Z = 4, μ(Mo Kα) = 0.215 mm-1, Dcalc = 1.1526 g/cm3, 14038 reflections measured (12.42° ≤ 2Θ ≤ 52.74°), 3448 unique (Rint = 0.0223, Rsigma = 0.0182) which were used in all calculations. The final R1 was 0.0337 (I≥2u(I)) and wR2 was 0.0927 (all data). The free radical scavenging activities of all three compounds were assayed using DPPH, FRAP, and OH assays. According to results obtained, compound 2 shows effective DPPH- (IC50 = 22.69±0.14 μg/mL), FRAP+ (IC50 = 28.44±0.12 μg/mL), and OH- (IC50 = 27.97±0.16 μg/mL) scavenging activities compared with compounds 1 and 3 but less than standard antioxidant compound Trolox (TRO). Additionally, theoretical calculations for the three complexes were performed by using density functional theory (DFT) calculations at the B3LYP/6-31++G(2d,2p) level in the ground state to obtain an optimized geometrical structure and to perform an electronic, molecular electronic potential surface and natural bond orbital (NBO) analysis. The geometrical calculation obtained was found to be consistent with the experimental geometry. Further analysis was conducted using the in silico technique to predict the drug likeness, molecular and ADME properties of these molecules.